2014
DOI: 10.1186/ar4494
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a and its regulator miR-24 link senescence and chondrocyte terminal differentiation-associated matrix remodeling in osteoarthritis

Abstract: IntroductionRecent evidence suggests that tissue accumulation of senescent p16INK4a-positive cells during the life span would be deleterious for tissue functions and could be the consequence of inherent age-associated disorders. Osteoarthritis (OA) is characterized by the accumulation of chondrocytes expressing p16INK4a and markers of the senescence-associated secretory phenotype (SASP), including the matrix remodeling metalloproteases MMP1/MMP13 and pro-inflammatory cytokines interleukin-8 (IL-8) and IL-6. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 56 publications
2
147
0
1
Order By: Relevance
“…On the other hand, by interfering with MDM2 (mouse double minute 2)‐dependent degradation of p53, p14/p19 ARF controls p53/p21 WAF1 ‐induced G1 or G2 cell cycle arrest (Gil & Peters, 2006). Remarkably, using knockout mice models for this locus, it was possible to reveal that these senescence features could be associated with the terminal differentiation program in some specific cell types including keratinocytes (Paramio et al ., 2001; Bachoo et al ., 2002), chondrocytes (Philipot et al ., 2014), myofibers (Pajcini et al ., 2010), and also megakaryocytic cells (Muñoz‐Espín & Serrano, 2014). Megakaryocytic cells, myeloid‐derived immune cells from which blood platelets originate, are required for wound healing and immune responses (Besancenot et al ., 2010), opening new avenues to explore features of senescence in other types of immune cells.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…On the other hand, by interfering with MDM2 (mouse double minute 2)‐dependent degradation of p53, p14/p19 ARF controls p53/p21 WAF1 ‐induced G1 or G2 cell cycle arrest (Gil & Peters, 2006). Remarkably, using knockout mice models for this locus, it was possible to reveal that these senescence features could be associated with the terminal differentiation program in some specific cell types including keratinocytes (Paramio et al ., 2001; Bachoo et al ., 2002), chondrocytes (Philipot et al ., 2014), myofibers (Pajcini et al ., 2010), and also megakaryocytic cells (Muñoz‐Espín & Serrano, 2014). Megakaryocytic cells, myeloid‐derived immune cells from which blood platelets originate, are required for wound healing and immune responses (Besancenot et al ., 2010), opening new avenues to explore features of senescence in other types of immune cells.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…OA progression is driven by inflammatory cytokines that initiate a cascade of matrix degradation, and the prominent role for SASP factors such as matrix metalloproteinase 13 (MMP‐13) and interleukin 1 alpha (IL‐1α) implicates senescent cells in the joint as a source of these catabolic molecules (Loeser, Collins & Diekman, 2016). The functional role of p16 INK4a in cartilage aging and OA is less clear, although knockdown and overexpression studies in cultured chondrocytes have confirmed that p16 INK4a expression is associated with the production of catabolic factors involved in dedifferentiation and OA (Philipot et al., 2014; Zhou, Lou & Zhang, 2004). Further evidence that non‐cell‐autonomous effects of senescence contribute to OA has come from a recent study showing that selective elimination of senescent cells can mitigate the development of OA (Jeon et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability and senescence are characterized by a loss of function and integrity, which contribute to the progressive degeneration of tissues (25,26). The cell viability and senescence of chondrocytes were determined under oxidative stress conditions mediated by H 2 O 2 or AA pretreatment using an MTT assay or the SA-β-gal assay, as shown in Fig.…”
Section: Aa Protects Chondrocytes From H 2 O 2 -Induced Loss Of Viabimentioning
confidence: 99%